Aplikasi Penggajian Karyawan Pada CV System Comutama - Bayu Kusumo (Informatika Universitas Siliwangi, 2020)
CV System Comutama is a business entity engaged in the sale of computer accessories. The payroll system contained in the CV System Comutama has not been carried out to the full potential for it requires a payroll application that can support the delivery of data more effectively and efficiently. The purpose of this research is to design employee payroll applications on the CV System Comutama effectively and efficiently, facilitate the financial department to be able to calculate employee payroll quickly and minimize errors and to facilitate the achievement of reports that are fast, accurate, valid, effective and efficient. The research method used is the grounded research method to collect data and analyze data at the same time. The modeling system used is the Data Flow Diagram (DFD) method using the java programming language while the database uses MySQL. With the employee payroll application is expected to facilitate the calculation of employee salaries and provide employee salary data reports that are stored neatly, safely, and accurately in a database that is systematic.